2022
DOI: 10.3390/polym14061192
|View full text |Cite
|
Sign up to set email alerts
|

An Industrial Case for Polypropylene Nanocomposite Foams: Lightweight, Soundproof Exterior Automotive Parts

Abstract: Lightweighting is a challenge for the automotive industry, and foaming is a key technology used to address this problem. A new practical approach is studied to regulate the cell formation of copolymer polypropylene (co-PP) by utilizing graphene nanoplatelets (xGnP) as a process aid during foam injection molding. The approach was designed to enable process freedom to tune part performance by adjusting the amount of xGnP masterbatch. Two different levels of 1–2 wt % xGnP and 0.25–0.35 wt % supercritical fluid (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Self‐polymerization products destroy the aggregation of PP molecular chains and make PP molecular chains slip more easily during compression. [ 47 ]…”
Section: Resultsmentioning
confidence: 99%
“…Self‐polymerization products destroy the aggregation of PP molecular chains and make PP molecular chains slip more easily during compression. [ 47 ]…”
Section: Resultsmentioning
confidence: 99%
“…Isotactic polypropylene is one of the most used polymers in transportation due to its low density, which allows for the production of lightweight materials [5,6]. The possibility to control the properties of isotactic polypropylene (iPP) parts in the injection molding process can be a way to reduce the environmental impact of plastic.…”
Section: Introductionmentioning
confidence: 99%
“…[1], [2] Different studies have shown that in the case of a 10 % in car weight reduction, fuel consumption, and emissions may be decreased by 6 % to 8 % and 5 % to 6 %, respectively. [3] Using polymer help to reduce the vehicle weight, impacting directly in the reduction of fuel consumption and gas emissions. [4] Polyolefins are polymer materials that are vastly used in the automotive industry, both in interior and exterior applications.…”
Section: Introductionmentioning
confidence: 99%